UPAYA PENGENDALIAN TEKANAN DARAH PADA PENDERITA HIPERTENSI MELALUI GUIDED IMAGERY DI KELURAHAN BINTARO KOTA MATARAM - Dewi Nur Sukma Purqoti; Baik Heni Rispawati; Harlina Putri Rusiana; Ernawati Ernawati; Baiq Rulli Fatmawati; Marthilda Suprayitna (Abdi Masyarakat, 2020)
Hypertension or high blood pressure is a disease of the heart and blood vessels characterized by an increase in systolic blood pressure of more than 140 mmHg and diastolic more than 90 mmHg which can result in increased morbidity and mortality. Hypertension is commonly found in the elderly, hypertension can be treated using pharmacology and non-pharmacology, one of which is the Guided Imagery technique. The purpose of this service activity is to increase public knowledge about the basic concepts of hypertension and how to control it. The method used in this activity is to provide counseling on the basic concepts of hypertension and how to control it in non-pharmacological form in the form of Guided Imagery technique. The results of this activity obtained that the majority of participants were over 50 years of age, mostly elementary school education, the sex of the majority of women there was an increase in knowledge after health education. After the implementation of this service, it is hoped that the community will carry out the Guided Imagery technique routinely to control blood pressure and the introduction of non-pharmacological management should be carried out as a preventive for hypertension in the community.